Analisis Konten Instagram Radio Elbayu yang Efektif Untuk Memikat Generasi Z - Gymnastiar Kamal Rafii; Nadilla Putri Anjelayni (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Social Media Instagram is a very famous application that is used by various audiences. Instagram is a very famous social media platform and is used by all audiences. One of them is in generation Z, because this platform has many features that can support users, for example sharing information or content and even being able to interact with friends, or even sharing stories and photo posts. So Instagram is very suitable to be used as social media to introduce people. Just like researchers took research to analyze the existence of Instagram content that is effective in attracting generation Z. Because in this case radio Elbayu is not yet known to generation Z. radio Elbayu only recommends radio that still uses AM frequencies. And the listeners are only elderly, the Z generation doesn't know or understand it yet. So with the Instagram platform that can create this content it can attract or add new followers. So that in this way we can still maintain the unique characteristics of Elbayu radio, namely radio broadcasts with AM frequencies and also Elbayu radio can keep up with the times by creating content on Instagram so that generation Z is more interested and gets to know Elbayu. Namely, the content is about Gresik and Surabaya, such as recommendations for tourist attractions, historical places, and much more